2015
DOI: 10.1007/s10340-015-0697-4
|View full text |Cite
|
Sign up to set email alerts
|

Contact behaviour and mortality of wireworms exposed to six classes of insecticide applied to wheat seed

Abstract: Insecticide-treated seed is commonly used to manage wireworms, with insecticide toxicity generally being deduced from crop stand protection rather than from directly observed wireworm responses. We observed the behaviour of larvae of two economic elaterids exposed to wheat seeds treated with 11 insecticides at various rates or combinations in a soil environment. Wireworms were exposed for 3 or 24 h, and the post-contact health and mobility of 1030 larvae that contacted seeds were assessed (bi)weekly for 12-42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Further optimization of this pheromone lure could ameliorate the high-cost and labor barriers associated with integrating pheromone tactics into root crop production systems. Novel methods of monitoring and managing wireworm pests are crucial because common insecticide treatments used on these crops are being scrutinized or banned for their deleterious environmental and human health effects (Saunders et al 2012, Douglas and Tooker 2015, van Herk et al 2015, Ubaid ur Rahman et al 2021). Advancements in pheromone-baited trap deployment will allow for more robust monitoring programs for M. communis and, subsequently, the development of IPM strategies that have previously been unrealistic for growers with detrimental wireworm populations.…”
Section: Resultsmentioning
confidence: 99%
“…Further optimization of this pheromone lure could ameliorate the high-cost and labor barriers associated with integrating pheromone tactics into root crop production systems. Novel methods of monitoring and managing wireworm pests are crucial because common insecticide treatments used on these crops are being scrutinized or banned for their deleterious environmental and human health effects (Saunders et al 2012, Douglas and Tooker 2015, van Herk et al 2015, Ubaid ur Rahman et al 2021). Advancements in pheromone-baited trap deployment will allow for more robust monitoring programs for M. communis and, subsequently, the development of IPM strategies that have previously been unrealistic for growers with detrimental wireworm populations.…”
Section: Resultsmentioning
confidence: 99%
“…This means that fewer insecticides need to be applied as foliar treatment, resulting in lower costs and reduced impacts on non-target species and the environment. At the same time, apart from the good effect of cyantraniliprole on black cutworm, other studies have not shown satisfactory efficacy of these insecticides on wireworms [74,75]. This means that seed treatments with cyantraniliprole provide some initial maintenance of plant density, but do not reduce wireworm populations and do not provide protection for the entire vegetation [75].…”
Section: Candidates For the Replacement Of Neonicotinoidsmentioning
confidence: 99%
“…When spinosad is used, adverse effects on bee communities [84] and bumblebees [85] are minimal when exposed to real concentrations of insecticides that would be expected in the environment. Van Herk et al [74] state that treatment of wheat seeds with spinosad under laboratory conditions resulted in transient morbidity of larvae, which later recovered after treatment. Another laboratory experiment showed that spinosad at doses of 3.5 and 5 mg/kg of seed applied to maize seed achieved an efficacy on wireworms of about 70% [76].…”
Section: Candidates For the Replacement Of Neonicotinoidsmentioning
confidence: 99%
“…When exposed to sublethal amounts of insecticides, wireworms show a range of different intoxication symptoms (Grove et al 2000, Vernon et al 2008, van Herk and Vernon 2013a). These symptoms vary depending on both the type and dose of chemical they are exposed to (van Herk et al 2008, 2015, Vernon et al 2008), and can be used to determine the presence of insecticide residues in field soil (e.g., Lange and Carlson 1956). For example, in a previous laboratory study, intoxication symptoms observed in larvae of Agriotes obscurus L. placed in field soil treated with bifenthrin the previous year were used to predict residue concentrations (van Herk et al 2013).…”
Section: Introductionmentioning
confidence: 99%